2007
DOI: 10.1158/1535-7163.mct-07-0312
|View full text |Cite
|
Sign up to set email alerts
|

Exemestane's 17-hydroxylated metabolite exerts biological effects as an androgen

Abstract: Aromatase inhibitors (AI) are being evaluated as longterm adjuvant therapies and chemopreventives in breast cancer. However, there are concerns about bone mineral density loss in an estrogen-free environment. Unlike nonsteroidal AIs, the steroidal AI exemestane may exert beneficial effects on bone through its primary metabolite 17-hydroexemestane. We investigated 17-hydroexemestane and observed it bound estrogen receptor A (ERA) very weakly and androgen receptor (AR) strongly. Next, we evaluated 17-hydroexemes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
1
47
0
1
Order By: Relevance
“…Characterization of these resistant lines showed that LTEDaro, TþLET R, and TþANA R cells contained a constitutively active ER that did not require estrogen for activation (Masri et al, 2008). Although EXE has previously been shown to act as an androgen (Ariazi et al, 2007), studies from our laboratory demonstrate the estrogenlike activity of EXE. Based on genome-wide microarray analysis, a high correlation was seen between EXE-Only (EXE O, hormone-free) and T-treated AI-resistant lines.…”
Section: A Global Way To View the Data-er As The Major Player Of Acqumentioning
confidence: 74%
“…Characterization of these resistant lines showed that LTEDaro, TþLET R, and TþANA R cells contained a constitutively active ER that did not require estrogen for activation (Masri et al, 2008). Although EXE has previously been shown to act as an androgen (Ariazi et al, 2007), studies from our laboratory demonstrate the estrogenlike activity of EXE. Based on genome-wide microarray analysis, a high correlation was seen between EXE-Only (EXE O, hormone-free) and T-treated AI-resistant lines.…”
Section: A Global Way To View the Data-er As The Major Player Of Acqumentioning
confidence: 74%
“…The limited literature available describes 17β-dihydroexemestane (17β-DHE) as a prominent phase I EXE metabolite possessing both anti-aromatase and androgen agonistic activities in vitro [22, 2630]. One study concluded that 17β-DHE concentrations were approximately 35–40% those of the parent drug in the plasma of healthy individuals taking EXE while another smaller study found that the amount of 17β-DHE relative to EXE in human plasma varied five-fold in a pool of only three participants [27, 31].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the course of this study, we recognized several factors complicating the interpretation of our results. First, as noted earlier, exemestane and its principal metabolite have weak androgenic activity (Zaccheo et al 1991;Ariazi et al 2007). Furthermore, inhibition of aromatase has been shown to increase circulating levels of endogenous testosterone (Baravalle et al 2006).…”
Section: Discussionmentioning
confidence: 81%